1986
DOI: 10.1002/app.1986.070320320
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing polyimide cure using infrared spectroscopy and a factorial design

Abstract: SynopsisThe cure of a polyimide derived from pyromellitic dianhydride (PMDA) and oxydianiline (ODA) has been studied using infrared spectroscopy. A factorial experimental design, combined with regression analysis, was used to find the optimum curing conditions. It was shown that five micron films can be cured by heating a t 230-250°C for times of five minutes or longer, while samples cured initially a t 150°C did not cure completely when heated to higher temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Previously, thin ®lms of insoluble polyimides were prepared from their soluble precursors, poly(amic acid)s, and thermally imidized at 300°C with the release of water. The quality of those polyimide thin ®lms is inferior, 4,5 to that of thin ®lms of organo-soluble polyimides such as a polyimide based on 1,4-bis(3,4-dicarboxyphenoxy) benzene (HQDPA) and 2,2'-dimethyl-4,4'-methylene dianiline (DMMDA), which can be easily prepared by spray coating. This polyimide is imidized completely, 6 so that annealing may not result in further imidization.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, thin ®lms of insoluble polyimides were prepared from their soluble precursors, poly(amic acid)s, and thermally imidized at 300°C with the release of water. The quality of those polyimide thin ®lms is inferior, 4,5 to that of thin ®lms of organo-soluble polyimides such as a polyimide based on 1,4-bis(3,4-dicarboxyphenoxy) benzene (HQDPA) and 2,2'-dimethyl-4,4'-methylene dianiline (DMMDA), which can be easily prepared by spray coating. This polyimide is imidized completely, 6 so that annealing may not result in further imidization.…”
Section: Introductionmentioning
confidence: 99%
“…This method involves reacting a dianhydride and a diamine at ambient conditions in a dipolar aprotic solvent such as N-methylpyrrolidinone (NMP) or N,Ndimethylacetamide (DMAc) to yield an intermediary product (polyimide precursor) called poly(amic acid) (PAA), which is cyclized into the final polyimide, by thermal treatment. However, this process has several problems such as emission of volatile byproducts and the storage instability of the poly(amic acid) intermediate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the actual degree of imidisation depends on the heating cycle, there is substantial evidence that the polymer must be heated to near 300°C to achieve quantitative or nearly quantitative cyclisation [67][68][69][70]. The recent study on thin films, however, claims that 99% imidisation can be achieved in thin films at 230-250°C [60]. It should be pointed out that the mechanism for the depolymerisation reaction during thermal imidisation is identical to that for the reaction during storage at ambient temperature.…”
Section: Mechanism Of Thermal Imidisationmentioning
confidence: 98%
“…5.um thick, of the poly(amic acid) prepared from DOPE and PMDA [60]. It was found that degrees ofimidisation of 97-99% could be achieved by heating the samples at 230-250°C for 10 minutes.…”
Section: Kinetics Of Thermal Imidisationmentioning
confidence: 99%
See 1 more Smart Citation